Optogenetic control of nuclear protein import in living cells using Light-Inducible Nuclear localization Signals (LINuS) - Wehler, Pierre; Niopek, Dominik; Eils, Roland; Di Ventura, Barbara (Current protocols in chemical biology, 2016)
Many biological processes are regulated by the timely import of specific proteins into the nucleus. The ability to spatiotemporally control the nuclear import of proteins of interest therefore allows study of their role in a given biological process as well as controlling this process in space and time. The light-inducible nuclear localization signal (LINuS) was developed based on a natural plant photoreceptor that reversibly triggers the import of proteins of interest into the nucleus with blue light. Each LINuS is a small, genetically encoded domain that is fused to the protein of interest at the N or C terminus. These protocols describe how to carry out initial microscopy-based screening to assess which LINuS variant works best with a protein of interest.